Integrating Litopenaeus vannamei into Dicentrarchus labrax hypersaline earthen ponds improves productivity and farm profitability: evaluating shrimp performance and economic viability under the effect of bile acid supplementation - Tamer El-Sayed Ali; Ashraf I. G. Elhetawy; Eenas Abdullah Hamad Ateeyah; Ahmed M. F. Sultan; Mohamed M. Zayed; Mohamed M. Abdel-Rahim (Aquaculture International, 2026)

Exploring the effect of bronopol exposure length on the suppression of Aeromonas hydrophila infection in nile tilapia (Oreochromis niloticus L.) - Zizy I. Elbialy; Eman M. Moustafa; Amira A. Omar; Abdallah S. Salah; Ahmed Elsheshtawy; Mohammed M. Zayed; Marwa F. Abdel-Kader; Hani Y. Labib; Hossam I. Kadira; Dina B. Barsem; Ahmed E. Elshafey; Sayed M. Aboleila; et al. (Veterinary Research Communications, 2026)

Corrigendum to “Innovative chrysotile/polyamide nanotextile filter for sustainable treatment of aqueous solutions and real wastewater: Fabrication, characterization, and performance evaluation” [J. Water Process Eng. 69 (2025) 106727] - Ahmed M. Zayed; Ahmed H. Ragab; Saedah Rwede AL-Mhyawi; Najla F. Gumaah; Mostafa A. Masoud; Amal H. El Maghrabi; Mohmmed M. El-Rabiee; Mohamed H. Abdelaziz; Bahaa S. Metwally (Journal of Water Process Engineering, 2025)

Innovative chrysotile/polyamide nanotextile filter for sustainable treatment of aqueous solutions and real wastewater: Fabrication, characterization, and performance evaluation - Ahmed M. Zayed; Ahmed H. Ragab; Saedah Rwede AL-Mhyawi; Najla F. Gumaah; Mostafa A. Masoud; Amal H. El Maghrabi; Mohmmed M. El-Rabiee; Mohamed H. Abdelaziz; Bahaa S. Metwally (Journal of Water Process Engineering, 2025)

HPMC-Zein Film-forming Gel Loaded with 5-Fluorouracil Coupled with CO2 Laser Dermabrasion for Managing Stable Vitiligo - Heba A. Abou-Taleb; Mohamed S. Mohamed; Gamal M. Zayed; Lamiaa N. Abdelaty; Mahmoud A. Makki; Hazem L. Abdel-Aleem; Mohamed A. El-Mokhtar; Helal F. Hetta; Nidaa Abdullah; Mohammed S. Saddik (AAPS PharmSciTech, 2024)

Fusing Genotype and Soil Organic/Inorganic Amendment to Improve Saline-sodic Properties and Rice Productivity - Osama A. M. Ali; Bassiouni A. Zayed; Moamen M. M. Abou El-Enin; Aly F. El Sheikha; Ahmed M. S. Kheir; Yasser A. El-Tahlawy; Wael M. Nada; Ahmed Shaaban (Journal of Soil Science and Plant Nutrition, 2024)
Soil salinization and sodification have become a considerable threat to sustainable crop production for food security. The efficient biological practice in rice cropping systems, besides modulating saline-sodic soil properties using different amendments, is a necessary tactic to accelerate reclamation. This research aimed to evaluate the potential ameliorative effect of seven organic/inorganic amendments addition on soil properties and the differential responses of three rice genotypes under saline-sodic soil conditions at north of Egypt. A 2-year (2019 and 2020) field experiment was conducted with three rice genotypes, viz., Sakha 106, Giza 179, and Egyptian hybrid rice 1 (EHR1) cultivated in saline-sodic-affected soil amended with seven organic/inorganic amendments, i.e. , gypsum, rice straw compost (RSC), farmyard manure (FYM), sulfur, sulfuric acid, calcium superphosphate, and rice husk beside control (unamended soil). This experimental design was a two-factor strip plot with randomized complete blocks with four replications. The morpho-physiological (SPAD chlorophyll , water content, leaf area index, and shoot dry weight) and biochemical (catalase (CAT) activity, proline content, carbohydrates, leaf sodium (Na + ) and potassium (K + ), and Na + /K + ratio) responses, the associated soil physico-chemical and microbial properties, yield, and its components were determined. RSC, gypsum, or sulfur were the most effective amendments in ameliorating saline-sodic soil properties by significantly reducing electrical conductivity, bulk density, and pH compared to the control and initial soil. Gypsum, RSC, FYM, or sulfur amendments significantly decreased the soil Na + by 14.2, 11.7, 9.1, and 8.3%; sodium adsorption ratio by 14.9, 12.6, 10.4, and 8.7%; and exchangeable sodium percentage by 13.5, 11.5, 9.3, and 8.2%, respectively, over both seasons compared with control. The organic amendments surpassed inorganic regarding microbial biomass carbon, soil respiration rate, and dehydrogenase activity with the superiority of RSC, FYM, and rice husk over the control treatment. These soil restorations were favorably reflected in morpho-physio-biochemical parameters, yield, and its components for all the tested rice genotypes. The EHR1 is the superior genotype in terms of ion (Na + and K + ) selectivity, CAT activity, possessing lower proline and higher morpho-physiological responses, and productivity. The EHR1 had a considerable physiological effect on saline-sodic soil stress, producing higher yield (7.70 and 7.50 t ha −1 ) after treating with RSC or gypsum. This indicates that RSC outperforms other amendments in improving saline-sodic soils and enhancing rice productivity. Overall, a single application of rice straw compost (organic amendment) and gypsum or sulfur (inorganic amendment) is a viable sustainable approach for modulating saline-sodic soil’s physico-chemical and microbial properties and for boosting rice’s agronomic and physiological responses in an arid environment.

The effect of mixture inhomogeneity and turbulence on the flame front curvature and flame surface density of turbulent planar flames of natural gas - Hazem M. Al-Bulqini; Mahmoud M.A. Ahmed; Ayman M. Elbaz; Mohamed F. Zayed; William L. Roberts; Mrinal Juddoo; Assaad R. Masri; Mohy S. Mansour (Fuel, 2024)

Effectiveness of DNA barcoding, SCOT markers and phytochemical characterization in biodiversity assessment of some Zea mays hybrids - Rehab M. Rizk; Ehab M. Zayed; Ali H. Amin; Ahmad A. Omar; Hesham F. Oraby (South African Journal of Botany, 2024)

Description of phenotype, grain quality, molecular fingerprinting, and biodiversity using DNA barcoding of some elite rice genotypes - Ahmad A. Omar; Ehab M. Zayed; Hesham F. Oraby; Nehal Z. Elnaggar; Mohamed M.A. Elashtokhy; Mostafa M. Basuoni; Ali Osman; Sahar A.M. Shamseldin; Kotb A. Attia; Azza H. Mohamed (South African Journal of Botany, 2023)

Co-expression of candidate genes regulating growth performance and carcass traits of Barki lambs in Egypt - Nasser Ghanem; Mohamed Zayed; Ismail Mohamed; Mona Mohammady; M. F. Shehata (Tropical Animal Health and Production, 2022)
Sheep are considered one of the main sources of animal protein in Egypt and the producers of sheep mutton eagers to find biological criteria for selecting fast-growing lambs that reach market weight early. Therefore, the present study aimed to find a link between the expression profile of selected candidate genes with growth performance and carcass traits of Barki lambs. Thirty-eight Barki lambs were kept and fed individually after weaning till 12 months of age and were divided into 3 groups according to growth performance (fast, intermediate, and slow-growing). Three samples were taken from different body tissues (eye muscle, liver, and fat tail) of each group, directly during slaughtering and stored at − 80 °C until RNA isolation. Real-time PCR was used to profile selected candidate genes (RPL7, CTP1, FABP4, ADIPOQ, and CAPN3) and GAPDH was used as a housekeeping gene. The results indicated that the final body weight was significantly ( P ≤ 0.05) greater in the fast (49.9 kg) and intermediate (40.7 kg) compared to slow-growing animals (30.8 kg). The hot carcass weight was heavier ( P ≤ 0.05) in the fast and intermediate-growing (24.57 and 19.07 kg) than slow-growing lambs (15.10 kg). The blood profiles of T3 and T4 hormones in addition to other parameters such as total protein, total lipids, and calcium level showed no clear variations among different experimental groups. At the molecular level, our data demonstrated upregulation of genes involved in protein biosynthesis (RPL7), fatty acid oxidation (CPT1), and lipolysis (FABP4) in the fast and intermediate-growing lambs in all studied tissues which facilitate protein accretion, energy expenditure, and fatty acid partitioning required for muscle building up. Moreover, the expression profile of the gene involved in muscle development (CAPN3) was increased in fast and intermediate-growing compared to slow-growing lambs in order to support muscle proper development. On the other hand, a candidate gene involved in lipogenesis (ADIPOQ) was expressed similarly in fat and liver tissues; however, its expression was increased in muscles of fast and intermediate-growing lambs compared to slow-growing animals. In conclusion, the current study indicated that the expression profile of genes involved in metabolic activities of liver, muscle, and adipose tissue is linked with the growth performance of lambs although no variations were detected in blood parameters. This provides an evidence for the importance of co-expression of these genes in body tissues to determine the final body weight and carcass characteristics of Barki sheep.

Hibiscus sabdariffa L.: phytoconstituents, nutritive, and pharmacological applications - Mohamed A. Salem; Ahmed Zayed; Magy E. Beshay; Mirna M. Abdel Mesih; Reem F. Ben Khayal; Fady A. George; Shahira M. Ezzat (Advances in Traditional Medicine, 2022)

Bioprocesses optimization and anticancer activity of camptothecin from Aspergillus flavus, an endophyte of in vitro cultured Astragalus fruticosus - Ashraf S. A. El-Sayed; Rawia A. Zayed; Ashraf F. El-Baz; Wafaa M. Ismaeil (Molecular Biology Reports, 2022)

Dietary Lactobacillus acidophilus ATCC 4356 Relieves the Impacts of Aflatoxin B1 Toxicity on the Growth Performance, Hepatorenal Functions, and Antioxidative Capacity of Thinlip Grey Mullet (Liza ramada) (Risso 1826) - Malik M. Khalafalla; Nahed F. A. Zayed; Asem A. Amer; Ali A. Soliman; Amr I. Zaineldin; Mahmoud S. Gewaily; Aziza M. Hassan; Hien Van Doan; Wanaporn Tapingkae; Mahmoud A. O. Dawood (Probiotics and Antimicrobial Proteins, 2022)

Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos - Nicholas M. A. Smith; Boris Yagound; Emily J. Remnant; Charles S. P. Foster; Gabriele Buchmann; Michael H. Allsopp; Clement F. Kent; Amro Zayed; Stephen A. Rose; Kitty Lo; Alyson Ashe; Brock A. Harpur; et al. (Molecular Ecology, 2020)
The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele .

Tagetnoic acid, a new lipoxygenase inhibitor peroxy fatty acid from Tagetes minuta growing in Saudi Arabia - Sabrin R. M. Ibrahim; Gamal A. Mohamed; Rwaida A. Al Haidari; Amal A. El-Kholy; Mohamed F. Zayed; Maan T. Khayat (Natural Product Research, 2020)

Design, synthesis, and biological evaluation studies of novel quinazolinone derivatives as anticonvulsant agents - Mohamed F. Zayed; Hany E. A. Ahmed; Abdel-Sattar M. Omar; Adel S. Abdelrahim; Khaled El-Adl (Medicinal Chemistry Research, 2013)

The role of the pituitary-ovarian axis in the termination of early pregnancy in rabbits treated with ethinyl-oestradiol - M. A. Attia; H. F. P. Joosten; I. Zayed; A. Hoekstra (Archives of Toxicology, 1980)